Evaluasi Perencanaan dan Pengadaan Obat Menggunakan Analisis ABC–VEN di Rumah Sakit Mardi Waluyo Metro - Sitanggang, Andrianus Bilhot; Ginaris, Rifkarosita Putri; Nurahman, Alfina (PHARMADEMICA : Jurnal Kefarmasian dan Gizi, 2025)
The unguaranteed availability of medicines in hospitals can reduce the quality of healthcare services, hinder therapeutic processes, and increase the risk of adverse events for patients. Therefore, an effective medicine procurement planning strategy is needed to optimally meet clinical needs. This study aims to analyze drug procurement planning at the Pharmacy Installation of Mardi Waluyo Hospital Metro using the ABC-VEN method. The analysis was conducted on 453 drug items planned by the hospital. The results showed that the main category (U) dominated with 245 items (54.08%), the priority category (P) consisted of 137 items (30.24%), and the additional category (T) consisted of 71 items (15.68%). Medicines with the highest usage values were in group A, indicating the need for strict monitoring to prevent stockouts. However, groups B and C drugs also require attention since some are vital medicines despite their relatively low usage levels. These findings highlight the importance of applying the ABC-VEN method to support efficiency in drug management while ensuring continuity of hospital services.